Pengaruh Stres Kerja dan Konflik Kerja terhadap Kinerja Karyawan Di Rutgerswpf Indonesia - Wanudhyaria Hamarto (UniSadhuGuna Business School, 2019)
One determinant of progress of a company is owned resources. A company or an entity feels that the absence of quality resources, the company's goals will not be achieved. But often not realized, the company only makes employees or resources as a means to achieve its goals rather than as individuals who need for recognition and awards. This study aims to know and explain the effect of work stress and work conflict on employee performance, both partially and simultaneously. Moreover, to know which independent variables that most influence on employee performance. The type of research conducted in this research is the explanation using a quantitative approach to explain corelation the relationship between variables through hypothesis testing, where the method of analysis used is multiple linear regression analysis. The results of this study indicate how stressful conditions of work stress and work conflict on employee performance, where there is a direct relationship between work stress and work conflict on Employee Performance, and partially and simultaneously influenced on employee performance. While the independent variables that most influence on the performance of employees is work conflict.